The Methuen Drama guide to contemporary South African theatre - Middeke, Martin; Schnierer, Peter Paul; Homann, Greg (Bloomsbury Publishing, 2018)
South Africa has a uniquely rich and diverse theatre tradition which has responded energetically to the country's remarkable transition, helping to define the challenges and contradictions of this young democracy. This volume considers the variety of theatre forms, and the work of the major playwrights and theatre makers producing work in democratic South Africa
Includes bibliographical references and index
Previously issued in print: London: Bloomsbury Methuen Drama, 2015. Digital resource published 2018
Zielgruppe - Audience: Specialized